(untitled) (Proceedings of the International Conference on Future of Women, 2020)
The arrival of stark number of forcibly displaced refugees in Germany since 2015 has led to increased challenges in the mental health care system. The system was overburdened, and therefore innovative approaches to health care for refugees were necessary in order to gain knowledge about their expansion and admission to regular care. To increase knowledge of refugees regarding mental health services and to provide practical support, a manual for peer-to-peer counseling was developed at Charité University Medical Center Berlin and refugees were trained as peer counsellors. This paper aims to give an overview of previous peer support interventions published in literature and to also point out to the preliminary results from the intervention conducted at the Charité. Good practices and recommendations for peer interventions are provided. Qualitative interviews were conducted with the group participants, and results show that peer groups helped refugees in sharing experiences, in giving ideas for possible solutions, in building social/friendship networks, and in providing a safe place for discussions. The results of our study suggest that integrating gender-sensitive peer support approaches in the mental health services for refugees may benefit the public health by reducing both need and demand for these services.